Thyroid dysfunction in Greece: Results from the national health examination survey EMENO. - Paraskevi V Voulgari; Aliki I Venetsanopoulou; Natasa Kalpourtzi; Magda Gavana; Apostolos Vantarakis; Christos Hadjichristodoulou; Grigoris Chlouverakis; Grigoris Trypsianis; Yannis Alamanos; Giota Touloumi; EMENO study group (PLoS ONE, 2022)
Background Nationwide data on thyroid disease prevalence in Greece is lacking. Using the national health examination survey EMENO data resources, we aimed to estimate the prevalence of hypothyroidism and hyperthyroidism and associated risk factors in adults living in Greece. Methods A random sample of the adults (≥18 years) living in Greece was drawn by multi-stage stratified random sampling based on the 2011 census. During home visits, trained interviewers administered a standardized questionnaire to study participants. All participants answered questions concerning demographic parameters (e.g., age, sex, degree of urbanization, income) and questions concerning smoking habits, alcohol, dietary habits and psychological parameters such as anxiety and thyroid disease. Weighted logistic regression models were fitted to assess factors associated with thyroid disease. Results In total, 6006 individuals were recruited in the Greek Health Examination Survey EMENO (response rate 72%) of whom 5981 were eligible for this study. The prevalence of thyroid disease was 9%, where 0.4% was related to hyperthyroidism and 8.6% to hypothyroidism. The prevalence of thyroid disease was higher in women (14.9%) than men (2.7%) (p<0.001). The highest rates of thyroid disease were observed in former iodine-deficient areas. A decrease in the prevalence of thyroidopathies with increasing alcohol consumption was found. Thyroid disease was associated with anxiety in men. Multivariable regression analysis showed that age, geographic area, and smoking were related to thyroid disease. Conclusion The prevalence of thyroid disease in Greece is higher in women. Age, habits, and characteristics of geographic areas determine the distribution of thyroidopathies in Greece.